Al-‘Uyūb al-Ḥarakiyyah wa al-‘Uyūb al-Bayāniyyah ‘inda al-Jāḥiẓ - Muflihah Muflihah (LISANIA: Journal of Arabic Education and Literature, 2021)
Al-Jahiz is an Arabic linguist discussing ancient and modern linguistic theories, but most of the current generation ((Arabic linguists) do not know much about him. This study aimed to examine the concept of Al-Jahiẓ on disabilities of kinetics (Al-harakiyah) and disclosure (Al-Bayaniyah) in using language. The method used was descriptive qualitative which would describe and analyze in depth the concept of Al-Jahiẓ in terms of kinetics and disclosure disabilities. The primary data sources were collected through documentation of Al-Jahiz books and others that discussed his findings. Based on the results, it was concluded that: According to Al-Jahiẓ, disabilities of kinetics (Al-harakiyah) include the presence of several movements made by the speaker during speaking or speech indicating turbulence, instability and composure, such as clearing throat or coughing. While the disabilities of disclosure (Al-Bayaniyah) include Al- ‘Ayyu Al-ḥaṣru, Al-Bik’u, Al-Faḥmu, As-Salāṭotu, Al-Hażru.